VD_FINDINFO Arrêt / 2025 / 219 vom 13. August 2025 - VD Tribunal cantonal (2025)
ADMISSION DE LA DEMANDE, ÉVALUATION DE L'IMPOTENCE, ENQUÊTEEN GÉNÉRAL, NOUVELLE DEMANDE, MOTIF DE RÉVISION | 42 LAI, 17 LPGA, 9 LPGA, 37 RAI, 38 RAI